2013
DOI: 10.5194/hess-17-4453-2013
|View full text |Cite
|
Sign up to set email alerts
|

A paradigm shift in stormflow predictions for active tectonic regions with large-magnitude storms: generalisation of catchment observations by hydraulic sensitivity analysis and insight into soil-layer evolution

Abstract: Abstract. In active tectonic regions with large-magnitude storms, it is still difficult to predict stormflow responses by distributed runoff models from the catchment properties without a parameter calibration using observational data. This paper represents an attempt to address the problem. A review of observational studies showed that the stormflow generation mechanism was heterogeneous and complex, but stormflow responses there were simply simulated by a single tank with a drainage hole when the stormflowco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Soils on temperate vegetated hillslopes are permeable enough that most rainfall infiltrates, temporarily forming a perched water table above the bedrock or layers of low infiltration capacity (e.g., Anderson et al, 1997;Asano et al, 2002;McDonnell, 1990;Montgomery & Buffington, 1997;Noguchi et al, 1999;Uchida et al, 2002). When this perched water table extends to the upper hillslope during wet conditions, a lateral subsurface flow is typically generated along preferential flow paths or through pressure transmission, causing stream flow to increase suddenly (e.g., Anderson et al, 1997;Buttle & McDonald, 2002;Haga et al, 2005;McGuire & McDonnell, 2010;Sidle et al, 2000;Tani, 1997Tani, , 2013Turton et al, 1992;Uchida et al, 2004;Wienhöfer & Zehe, 2014). When hillslopes become saturated to the point that water storage is almost maximized, the shapes of the hyetograph and hydrograph become similar (Sidle et al, 2000;Tani, 1997Tani, , 2008Tani, , 2013Torres et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soils on temperate vegetated hillslopes are permeable enough that most rainfall infiltrates, temporarily forming a perched water table above the bedrock or layers of low infiltration capacity (e.g., Anderson et al, 1997;Asano et al, 2002;McDonnell, 1990;Montgomery & Buffington, 1997;Noguchi et al, 1999;Uchida et al, 2002). When this perched water table extends to the upper hillslope during wet conditions, a lateral subsurface flow is typically generated along preferential flow paths or through pressure transmission, causing stream flow to increase suddenly (e.g., Anderson et al, 1997;Buttle & McDonald, 2002;Haga et al, 2005;McGuire & McDonnell, 2010;Sidle et al, 2000;Tani, 1997Tani, , 2013Turton et al, 1992;Uchida et al, 2004;Wienhöfer & Zehe, 2014). When hillslopes become saturated to the point that water storage is almost maximized, the shapes of the hyetograph and hydrograph become similar (Sidle et al, 2000;Tani, 1997Tani, , 2008Tani, , 2013Torres et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…When this perched water table extends to the upper hillslope during wet conditions, a lateral subsurface flow is typically generated along preferential flow paths or through pressure transmission, causing stream flow to increase suddenly (e.g., Anderson et al, 1997;Buttle & McDonald, 2002;Haga et al, 2005;McGuire & McDonnell, 2010;Sidle et al, 2000;Tani, 1997Tani, , 2013Turton et al, 1992;Uchida et al, 2004;Wienhöfer & Zehe, 2014). When hillslopes become saturated to the point that water storage is almost maximized, the shapes of the hyetograph and hydrograph become similar (Sidle et al, 2000;Tani, 1997Tani, , 2008Tani, , 2013Torres et al, 1998). Theoretical studies of catchment hydrological behavior have suggested that the relative roles of hillslopes in catchment responses may change with the wetness condition of the catchment (Botter & Rinaldo, 2003;Robinson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…1.浸透流説と水みち説 Liang et al, 2011;Beven and Germann, 20131979Harman and Sivapalan, 2009Troch et al, 20031963 30cm Brutsaert, 2005Brutsaert, 1994Brutsaert, 20052013Freeze 1972 Freeze 1980Mosley, 19791988McDonnell, 1990Freeze 1962 1963 A 10 mm h -1 A 0.05 mm h -1 B 5 mm h -1 Kosugi, 1996HYDRUS 1D (Šim nek et al, 2013 0.5 0.2 -10 cm 1.7 6x10 -3 cm s -1 Fig. 3 Temporal changes in the distribution of volumetric water content in response to constant rainfall intensity of 10 mm h -1 calculated using a one-dimensional vertical form of the Richards equation.…”
Section: ⅳ. 斜面の流出機構に基づく土壌効果の 評価mentioning
confidence: 99%